Trustworthiness of digital records in government accounting system to support the audit process in Botswana. (15th February 2021) - Mosweu, Olefhile; Ngoepe, Mpho
Abstract : Purpose: The purpose of this study is to explore how the trustworthiness of digital records generated in an enterprise resource planning (ERP) system known as the government accounting and budgeting system (GABS) is maintained to support the audit process in the public sector of Botswana. Design/methodology/approach: This qualitative study used modern archival diplomatics as a theoretical framework to examine the procedures for authenticating digital accounting records in GABS to support the audit process in Botswana. Data were collected through interviews and documentary reviews. Findings: The study established that although GABS is not a record-keeping system, it generates digital records. In the absence of procedures, auditors rely on social and technical indicators (system application controls) to authenticate records. Research limitations/implications: The findings of the study are limited to the case study and cannot be generalised to other organisations. Practical implications: The findings of the study can inform the necessary measures that can be taken to ensure that digital records generated in ERPs are maintained authentic to support financial auditing processes. In addition, the paper also presents differing approaches by records managers, auditors and information technology specialists to evaluate the authenticity of records in digital systems, thus contributing to the literature about professional allies and competitors to archivists and records managers. Originality/value: This paper provides empirical evidence from an original study.